Simposium Kebudayaan Indonesia- Malaysia Ke -11 Bandung, Indonesia - Zainun, Zuraida (Universiti Sains Malaysia, 2012)
Effectiveness of Using Video of Physical Exercises in Adults with Balance Problems: A Preliminary Report